Provenance Trial of Eucalyptus oamaldulensls Dehn - Ghosh, R. C.; Gupta, B. N.; Shedha, M. D. (Indian Forester, 1977)
Eucalypius camaldulenasis has a wide range of distribution in Australis, and is very adaptive to different soil and climatic conditions. Provenance trials of this sipecies were undertaken at a number of centres in India including New Forest, Dehra Dun. Seeds of 12 provenances received from Australia were sown in the nursery and the seedlings raised from them were planted in Quartera block in July 1967. Periodical growth measurements of the plants were recorded and at the close of the experiment in 1975 data was also collected on the diameter of trees, weight of the main bole and branchwood and also the total weight of the leaves in respect of 7 provenances, 5 provenances which exhibited poor performance with regard to survival were not considered. Specific gravity of wood of these seven provenances was also worked out. Analysis of the data indicated that provenance S3 is significantly superior to the other proVenances Provenances S7, S3 and 51 showed significantly superior height and diameter growth and the total green weight of the trees compared to other provenances. A highly significant correlation coefficient between green weight of leaves and weight of total wood was found at 0.1 percent level of probability.